Stimulation of Unprimed Macrophages with Immune Complexes Triggers a Low Output of Nitric Oxide by Calcium-dependent Neuronal Nitric-oxide Synthase - Huang, Zhi (American Society for Biochemistry and Molecular Biology, 2012)
Immune complexes composed of IgG-opsonized pathogens, particles, or proteins are phagocytosed by macrophages through Fcγ receptors (FcγRs). Macrophages primed with IFNγ or other pro-inflammatory mediators respond to FcγR engagement by secreting high levels of cytokines and nitric oxide (NO). We found that unprimed macrophages produced lower levels of NO, which required efficient calcium (Ca(2+)) flux as demonstrated by using macrophages lacking selenoprotein K, which is required for FcγR-induced Ca(2+) flux. Thus, we further investigated the signaling pathways involved in low output NO and its functional significance. Evaluation of inducible, endothelial, and neuronal nitric-oxide synthases (iNOS, eNOS, and nNOS) revealed that FcγR stimulation in unprimed macrophages caused a marked Ca(2+)-dependent increase in both total and phosphorylated nNOS and slightly elevated levels of phosphorylated eNOS. Also activated were three MAP kinases, ERK, JNK, and p38, of which ERK activation was highly dependent on Ca(2+) flux. Inhibition of ERK reduced both nNOS activation and NO secretion. Finally, Transwell experiments showed that FcγR-induced NO functioned to increase the phagocytic capacity of other macrophages and required both NOS and ERK activity. The production of NO by macrophages is conventionally attributed to iNOS, but we have revealed an iNOS-independent receptor/enzyme system in unprimed macrophages that produces low output NO. Under these conditions, FcγR engagement relies on Ca(2+)-dependent ERK phosphorylation, which in turn increases nNOS and, to a lesser extent, eNOS, both of which produce low levels of NO that function to promote phagocytosis.